Remarks on nontrivial pullback attractors of the 2‐D Navier‐Stokes equations with delays. (13th November 2019) - Wang, Yongzhong; Yang, Xin‐Guang; Lu, Yongjin
Abstract : This paper is concerned with some further research on the pullback dynamics for 2‐D Navier‐Stokes equations with delays. By some new definition of generalized Grashof numbers, we presented some sufficient conditions when the pullback attractors of the 2‐D nonautonomous incompressible Navier‐Stokes equations with differential continuous delays become a single trajectory, which is a preparation for the fractal dimension of pullback attractors for our problem with constant or variable delays.